The clusters development as a factor of competitive advantage. (6th February 2006) - Pereira, Elisabeth T.; Fernandes, Antonio Jorge
This study examines the cluster concept and the importance of developing clusters to obtain and sustain competitive advantages, either as a regional competitive factor or to the level of industrial competitiveness.